From Founders’ Knowledge to Economic Value Capture in Academic and Employee Start-ups - Moeen, Mahka (Organization Science, 2026)
Economic value capture is crucial for entrepreneurial start-ups as it conditions the commercial viability of the technological opportunities underlying their founding. Start-ups vary in whether they capture value and, if so, whether through markets for product or technology. This study posits that value capture hinges on founders’ knowledge accumulated in their prior employment context, separating founders as academic scientists and former employees of industry firms. Academic founders bring scientific knowledge from universities, and within-industry employee founders carry industry-specific knowledge from their former employer. These differences provide the theoretical basis that the study empirically explores in U.S. medical device start-ups. Academic start-ups tend to capture value in markets for technology, whereas within-industry employee start-ups tend to capture value in markets for product. Further, variations in founders’ history and employment context can bridge scientific and commercial dimensions in knowledge profiles within academic and employee start-ups, shifting the resulting value capture pathway toward pioneering products. Funding: This work was supported by the Richard M. Schulze Family Foundation and the Ewing Marion Kauffman Foundation. Supplemental Material: The online appendix is available at https://doi.org/10.1287/orsc.2023.18121 .